Analisis Terhadap Keputusan Investasi pada Koperasi Syariah; Bagaimana Perkembangan Investasi pada Koperasi Syariah? - Fitri Maulida Husna; Chuzaimah Batubara (Universitas Muhammadiyah Enrekang, 2023)
Cooperatives are one example of a cooperative business that is managed by the community and is directed to the common good. Cooperatives can function as independent business entities at several levels of the economy, including channels of financial approval within the small and medium enterprise (MSMEs) ecosystem. This research is based on several articles from national and international media published between 2018 and 2022, we sampled various types of documents related to cooperatives as financial service providers using the concept of parity. Trends, opportunities and financial benefits are the main objectives of this research. Filiera is a type of cooperative organization based on sharia standards. The analytical method used in this research is course data analysis. The findings of this study indicate that the use of Islamic accounting principles, not through the quality of financial reporting, has a significant impact on investment decision making. The implications of this research include improving the operational performance of Islamic cooperatives and encouraging members’ interest in investing. The novelty of this research is the initial impetus for investing in Islamic cooperatives.